El lenguaje artístico de la Orden del Toisón de Oro, leyenda, signos y símbolos - Campos Sánchez-Bordona, María Dolores (Estudios humanísticos. Geografía, historia y arte, 1997)
This subject is an aproach to the study of the prestigious Ordre of Toison d'Or and the House of Borgoña troughout its legends, myths and symbols.